PENERAPAN MODEL PEMBINAAN CLKK (CONTOH, LATIHAN, KONTROL, KERJA MANDIRI) MENINGKATKAN HASIL BELAJAR MAHASISWA PGSD 2019 UNIMED DALAM MERENCANAKAN EVALUASI PENDIDIKAN BAHASA DAN SASTRA INDONESIA INDONESIA KELAS RENDAH TAHUN PEMBELAJARAN 2020/2021 - Masta Masrselina Sembiring; Irsan Rangkuti (Universitas Negeri Medan, 2020)
Abstract: The Implementation of CLKK Guidance Model (Example, Exercise, Control, Independent Cooperation) Improves Learning Outcomes of 2019 Unimed PGSD Students in Planning Evaluation of Indonesian Language and Literature Education Low Class 2020/2021 Learning Year. The purpose of this research is to improve the ability of PGSD FIP UNIMED students in plan Evaluation Tool for Learning Indonesian Language and Literature for Low Grade Elementary Schools in Low Grade Indonesian Language and Literature Education. This research is classified as a Classroom Action Research involving 40 students of class A PGSD FIP Unimed totaling 40 students. This research was conducted at Medan State University, PGSD Department. Implementation time in odd semester 2020/2021. This research design is in the form of Classroom Action Research using two cycles. The instrument used in this research is an assignment. The research stages started from the initial test on students which aimed to detect the problems that occurred. From the known problems, the CLKK Development Model Application (Example, Training, Control, Independent Work) is applied for cycle 1. The data analysis used to solve the problems presented in this study is descriptive analysis, namely explaining the direction of change, increasing change, and understanding student concepts. The results of the research on the pretest obtained an average value of 64.62, in Cycle I increased 85.62 and 90.62 in Cycle III and the category was satisfactory. From these results, a conclusion will be drawn that the CLKK Guidance Model (for example, training, control, independent work) can improve student abilities in planning evaluation tools for low grade elementary school Indonesian language and literature learning in the 2020/2021 learning year. The results of the research on the pretest obtained an average value of 64.62, in Cycle I increased 85.62 and 90.62 in Cycle III and the category was satisfactory. From these results, a conclusion will be drawn that the CLKK Guidance Model (for example, training, control, independent work) can improve student abilities in planning evaluation tools for low grade elementary school Indonesian language and literature learning in the 2020/2021 learning year. The results of the research on the pretest obtained an average value of 64.62, in Cycle I increased 85.62 and 90.62 in Cycle III and the category was satisfactory. From these results, a conclusion will be drawn that the CLKK Guidance Model (for example, training, control, independent work) can improve student abilities in planning evaluation tools for low grade elementary school Indonesian language and literature learning in the 2020/2021 learning year.Keywords: Model, CLKK, Evaluation, Indonesian Language, Low ClassAbstrak: Penerapan Model Pembinaan CLKK (Contoh, Latihan, Kontrol, Kerja Sama Mandiri) Meningkatkan Hasil Belajar Mahasiswa PGSD 2019 Unimed dalam Merencanakan Evaluasi Pendidikan Bahasa dan Sastra Indonesia Kelas Renda Tahun Pembelajaran 2020/2021. Tujuan penelitian ini adalah meningkatkan kemampuan mahasiswa PGSD FIP UNIMED dalam merencanakan Alat Evaluasi Pembelajaran Bahasa dan Sastra Indonesia SD Kelas Rendah pada Mata Kulian Pendidikan Bahasa dan Sastra Indonesia Kelas Rendah. Penelitian ini tergolong Penelitian Tindakan Kelas dengan melibatkan 40 mahasiswa kelas A PGSD FIP Unimed berjumlah 40 mahasiswa.Penelitian ini dilaksanakan di Universitas Negeri Medan, Jurusan PGSD. Waktu pelaksanaan pada semester ganjil 2020//2021. Desain penelitian ini berbentuk Penelitian Tindakan Kelas (Classroom ActionResearch) dengan menggunakan dua siklus. Instrumen yang digunakan dalam penelitian ini adalah berupa penugasan. Tahap-tahap penelitian dimulai dari tes awal pada mahasiswa yang bertujuan untuk mendeteksi permasalahan yang terjadi. Dari permasalahan yang telah diketahui maka diterapkan Penerapan Model Pembinaan CLKK (Contoh, Latihan, Kontrol, Kerja Mandiri) untuk siklus 1. Analisis data yang digunakan untuk menyelesaikan masalah yang disajikan dalam penelitian ini adalah analisis deskriptif yaitu menjelaskan arah perubahan, peningkatan perubahan, dan pemahaman konsep mahasiswa. Hasil penelitian pada pretes diperoleh nilai rata-rata 64,62, Siklus I meningkat 85,62 dan pada Siklus III 90,62 dan kaegori memuaskan. Dari hasil tersebut akan ditarik sebuah kesimpulan Model Pembinaan CLKK (Contoh, Latihan, Kontrol, Kerja Mandiri) dapat Meningkatkan Kemampuan Mahasiswa dalam Merencanakan Alat Evaluasi Pembelajaran Bahasa dan Sastra Indonesia SD Kelas RendahTahun Pembelajaran 2020/2021. Kata Kunci : Model, CLKK, Evaluasi, Bahasa Indonesia, Kelas Rendah